ANALISIS PENYUSUNAN ANGGARAN PENJUALAN PADA UMKM KULINER SEBLAK RANCAEKEK - Lia Nurjanah; Rachmat Agus Susanto (AKRUAL : Jurnal Akuntansi dan Keuangan, 2024)
This research was conducted because there was no budget in the financial records of Seblak Rancaekek Culinary MSMEs, especially the sales budget where the sales budget is a budget that plans the company's sales for the coming period. The sales budget is used as a company tool in planning and controlling the company's sales activities in order to achieve the desired optimal profit. The sales budget can be used as a reference in efforts to increase subsequent sales. In making sales forecasts, researchers compared 3 forecasting methods, namely Semi Average, Trend Moment, and Least Square and calculated the Standard Forecasting Error (SKP) for each method to determine the most appropriate method.